EFFECT OF POLLUTION ON DISSOLVED OXYGEN CONCENTRATION IN STREAM OF SHIVALIK HIMALAYAS A CASE STUDY: Life Sciences-Environmental Science - GAUTAM, D.K. (International Journal of Life Science and Pharma Research, 2011)
This paper addresses the effect of pollution on dissolved oxygen content (DO) in a Shivalik Himalayan stream during early hours of day in the summer season (May, 2009) – June 2010). The study showed that the Dissolved Oxygen in the stream is below 4mg/l in a stretch of 2600m and therefore water is not fit for public supply, bathing wildlife and fish culture.